1999
DOI: 10.1128/jvi.73.7.5787-5794.1999
|View full text |Cite
|
Sign up to set email alerts
|

Structural Constraints on RNA Virus Evolution

Abstract: The recently discovered hepatitis G virus (HGV) or GB virus C (GBV-C) is widely distributed in human populations, and homologues such as HGV/GBV-CCPZ and GBV-A are found in a variety of different primate species. Both epidemiological and phylogenetic analyses support the hypothesis that GB viruses coevolved with their primate hosts, although their degree of sequence similarity appears incompatible with the high rate of sequence change of HGV/GBV-C over short observation periods. Comparison of complete coding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 27 publications
5
59
0
1
Order By: Relevance
“…The totality of HBoV1 sequences collected worldwide by multiple groups show very low protein and nucleotide sequence diversity ( Table 2 and Figure 4A) [35,36]. In contrast, this single study found substantial diversity among HBoV2 and HBoV3, a fourth species (HBoV4), and extensive viral recombination (Figures 3, 4B, and 4C).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The totality of HBoV1 sequences collected worldwide by multiple groups show very low protein and nucleotide sequence diversity ( Table 2 and Figure 4A) [35,36]. In contrast, this single study found substantial diversity among HBoV2 and HBoV3, a fourth species (HBoV4), and extensive viral recombination (Figures 3, 4B, and 4C).…”
Section: Discussionmentioning
confidence: 79%
“…Recombination analyses. Similarity values based on Jukes-Cantor corrected nucleotide distances between full-length sequences were calculated using the program SequenceDist in the Simmonic2005 v1.6 Sequence Editor Package [35]. To assess similarity across the genomes, sequence scans were performed using a fragment length of 300 bases and an increment of 9 bases between fragments.…”
Section: Samplesmentioning
confidence: 99%
“…Various approaches have been developed to test for selection on non-coding regions [51] and to predict the secondary structure of RNA molecules [52,53], but to date their use has been limited in evolutionary analyses of viruses. Further development of these methods could improve our understanding of the role that RNA structures play in virus evolution [54].…”
Section: Parallel Evolution Beyond the Sequence Levelmentioning
confidence: 99%
“…4. Multiple constraints for variability have been evidenced in viral genomes (Simmonds and Smith 1999;Simmonds et al 2004). Therefore, many variants with one or few mutations that may confer biologically relevant, adaptive traits may not be represented in a mutant spectrum (under a set of environmental conditions) due to fitness costs.…”
Section: Fecunditymentioning
confidence: 99%